2008
DOI: 10.1097/ta.0b013e318184a9fe
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Impact of the Trauma Team Training Program in Tanzania

Abstract: After completion of TTT, there was a significant improvement in trauma resuscitation knowledge, based on results from a validated questionnaire. Trauma team performance was excellent when assessed with a novel trauma simulation assessment tool. Participants were very supportive of the course.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
64
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(64 citation statements)
references
References 9 publications
0
64
0
Order By: Relevance
“…Trauma resuscitation studies constitute extrapolated evidence (LOE 5) for cardiac arrest patients. One study in Tanzania, 461 2 studies in Trinidad and Tobago 462 and Ecuador, 463 and 1 study in Nigeria 464 reported that implementation of standard ATLS or trauma team training and modified trauma training programs were effective in developing trauma skill competencies in hospital providers. A study from Trinidad and Tobago 465 and 2 studies comparing Cambodia and Northern Iraq 466,467 demonstrated that the delivery of standard or appropriately modified ATLS training to the local community improved hospital mortality from trauma.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Trauma resuscitation studies constitute extrapolated evidence (LOE 5) for cardiac arrest patients. One study in Tanzania, 461 2 studies in Trinidad and Tobago 462 and Ecuador, 463 and 1 study in Nigeria 464 reported that implementation of standard ATLS or trauma team training and modified trauma training programs were effective in developing trauma skill competencies in hospital providers. A study from Trinidad and Tobago 465 and 2 studies comparing Cambodia and Northern Iraq 466,467 demonstrated that the delivery of standard or appropriately modified ATLS training to the local community improved hospital mortality from trauma.…”
Section: Consensus On Sciencementioning
confidence: 99%
“…Some previous studies in LRS have shown that multidisciplinary team training in simulated trauma and newborn resuscitations improved team performance and resuscitation knowledge and, in some cases, was shown to reduce mortality. [10][11][12][13][14][15] One of these studies found that a low-cost educational intervention can affect knowledge constructs among international teams. 10 Identification and removal of barriers to teamwork and efficiency of decision-making processes become more salient in LRS.…”
Section: What This Study Addsmentioning
confidence: 99%
“…Practical simulation can positively affect knowledge and confidence among trauma team members [10,17]. Trauma team organization has been shown to reduce the time to definitive surgery (18) and to reduce mortality [6,15].…”
Section: Discussionmentioning
confidence: 99%